Indonesia di Antara Masalah Etnis Rohingya dan Etnis Uighur, 2014-2019 - Rahmadanu Pradityo (Indonesian Perspective, 2020)
Indonesia’s foreign policy during the 2014-2019 period was quite dynamic. Out of many issues, two international issues received strong reactions Indonesian society including Rohingya ethnic group issue in Myanmar and the Uighur ethnic group issue in China. Protests against these two issues occurred in two different time periods in some regions of Indonesia, demanding the government to take firm actions regarding these issues. This paper examines Indonesia’s attitudes toward Rohingya ethnic group issue in Myanmar and the Uighur ethnic group issue in China based on constructivism paradigm using the theory of identity. This paper presents gaps in Indonesia’s identity and interests regarding these issues which led to different attitudes in responding to those issues.